A STUDY ON THE EVALUATION OF USER SATISFACTION WITH PREPAID AND POSTPAID ELECTRICITY SERVICES IN BIMA CITY - Hartawan, Hartawan; A Karim, Sugeng; Hasrul, Hasrul (Fakultas Teknik Universitas Negeri Makassar, 2023)
The goal of the research is to find out how happy people are with Bima Kota's prepaid and postpaid energy services. Quantitative methods are used in this study. The data used is primary data, which comes from giving surveys to the people being studied. All the people who use energy in the Nitu Village in Kota Bima are included in this study. Cluster random sampling is used to get the sample data, and there are 100 people in the group. The results of the study show that 1) Tangibles, Reliability, Responsiveness, Assurance, and Empathy variables have an effect on people who use prepaid electricity services where people are satisfied with the services provided; 2) Tangibles, Reliability, Responsiveness, Assurance, and empathy variables have an effect on people who use postpaid electricity services where people are satisfied with the services provided; and 3) the dimensions of tangibles, reliability, responsiveness, confidence, and emphasis So that means there is a difference in how happy people are with prepaid electricity versus postpaid energy. As for the confidence dimension, it has a t count > t table or a prob value > alpha 0.05, which means that there is no significant difference between respondents who paid for their electricity in advance and those who paid for it later. The positive mean difference means that the average satisfaction of people who paid for their electricity in advance is better than that of people who paid for their electricity later.